Examination of liver and muscle glycogen and blood glucose levels of Capoeta umbla (Heckel, 1843) living in Hazar Lake and Keban Dam Lake (Elazig, Turkey) - Coban, Mehmet Zulfu; Sen, Dursun (Academic Journals, 2011)
This study was conducted between December 2006 and November 2007 on Capoeta umbla fish species obtained from Hazar Lake and Keban Dam Lake (Elazig, Turkey). It was determined that the GSI values reached maximum in May and started decreasing after this month; the liver glycogen and condition factor values started decreasing after May when gonadal development is maximum. This decrease continued until June and then started increasing again. It was also determined that blood glucose values reached maximum when energy requirement is high and start to decrease after May when reproduction starts. In the summer, it was determined that glycogen and glucose reserves were at low levels when temperature is high. But they were at high levels at autumn and winter when the temperature is lower. Glycogen and glucose reserves generally showed parallel changes with oxygen reserves.
Keywords: Capoeta umbla; Hazar Lake; Keban Dam Lake; liver glycogen; muscle glycogen; blood glucose